Diversity of soil macrofauna on different pattern of sloping land agroforestry in Wonogiri, Central Java - MARKANTIA ZARRA PERITIKA; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO (Biodiversitas Journal of Biological Diversity, 2012)
Peritika MZ, Sugiyarto, Sunarto. 2012. Diversity of soil macrofauna on different pattern of sloping land agroforestry in Wonogiri, Central Java. Biodiversitas 13: 140-144. The purposes of this study were to determine the diversity level of soil macrofauna on different patterns of sloping land agroforestry, in Wonogiri District, Central Java, and to find out the relationship between environmental factorsand the level of soil macrofauna diversity. The study was conducted by sampling at three different patterns of agroforestry, namely: pattern of mixed agroforestry (PAC), pattern of teak agroforestry (PAJ), and the pattern of sengon agroforestry (PAS). The field sampling used two methods, namely pit fall traps to obtain above ground macrofauna, and hand sorting methods to obtain underground macrofauna, on land slope of 39%, 35%, and 27%. The data were collected to determine the diversity index of soil macrofauna; and theenvironmental factors were also measured. The relationship between environmental factors and the diversity index of soil macrofauna was presented in Pearson's correlation analysis. The results showed that the pattern of sloping land agroforestry in Wonogiri District, Central Java had different diversity index of soil macrofauna. The average diversity index of surface macrofauna was the PAC (0.710), PAS (0661), and PAJ (0.417). The average diversity index of underground macrofauna was the PAC (0.887), PAS (0.860), and PAJ (0.843). The diversity index of soil macrofauna in various patterns of sloping land agroforestry showed that there was a correlation with environmental factors.